2021
DOI: 10.1037/xge0001062
|View full text |Cite
|
Sign up to set email alerts
|

Conditionals and the hierarchy of causal queries.

Abstract: Recent studies indicate that indicative conditionals like "If people wear masks, the spread of Covid-19 will be diminished" require a probabilistic dependency between their antecedents and consequents to be acceptable (Skovgaard-Olsen et al., 2016). But it is easy to make the slip from this claim to the thesis that indicative conditionals are acceptable only if this probabilistic dependency results from a causal relation between antecedent and consequent.According to Pearl ( 2009), understanding a causal relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 113 publications
(397 reference statements)
1
8
0
Order By: Relevance
“…Counterfactual simulation explains causal judgements, whereas hypothetical simulation does not. This result extends recent work showing that people differentiate between indicative conditionals (level I) and counterfactual conditionals (level III), and that causal judgements align more closely with counterfactual judgements [43].…”
Section: (A) Implications For Theories Of Causalitysupporting
confidence: 88%
See 2 more Smart Citations
“…Counterfactual simulation explains causal judgements, whereas hypothetical simulation does not. This result extends recent work showing that people differentiate between indicative conditionals (level I) and counterfactual conditionals (level III), and that causal judgements align more closely with counterfactual judgements [43].…”
Section: (A) Implications For Theories Of Causalitysupporting
confidence: 88%
“…Most relevant to the question of how hypothetical and counterfactual judgements relate to causal judgements is a recent paper by Skovgaard-Olsen et al [43]. Across a series of six experiments, the authors show that people differentiate between indicative conditionals (if x happens then y happens) and counterfactual conditionals (if x had happened then y would have happened).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, research on conditional reasoning has shown that people’s assumptions about the causal structure (Bonnefond et al, 2014; Byrne, 1989; Byrne et al, 1999; Espino & Byrne, 2020) and their normative expectations about the frequency of events (Oaksford & Chater, 1994, 2003) affect what inferences people draw. Precisely what people infer from conditional statements is still very much under investigation (Barrouillet et al, 2008; Collins et al 2020; Khemlani & Johnson-Laird, 2013; Sebben & Ullrich, 2021; Skovgaard-Olsen et al, 2021). Given the tight relationship between conditionals and causality (e.g., Goldvarg & Johnson-Laird, 2001; Over et al, 2007), we suspect that inferences from conditional statements, just like inferences from explanations, may be illuminated by considering what role these statements play in communication (see also Evans, 2005; Johnson-Laird & Byrne, 2002; Sebben & Ullrich, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The relevant evidence comes from studies on how people reason about counterfactual conditionals (e.g. Lucas & Kemp, 2015;Sloman & Lagnado, 2005;Over et al, 2007;Rips, 2010;Rips & Edwards, 2013;Dehghani et al, 2012;Oaksford & Chater, 2007;Gerstenberg et al, 2013;Pfeifer & Tulkki, 2017;Byrne & Johnson-Laird, 2020;Skovgaard-Olsen et al, 2021). Counterfactual conditionals are statements such as "if Alice had lost the game, then she would have drawn a black ball from the first box" (Lewis, 1973b;Stalnaker, 1981;Hiddleston, 2005;Lassiter, 2017;Starr, 2019).…”
Section: A Formal Model Of Counterfactual Samplingmentioning
confidence: 99%